Efforts to Prevent Low Back Pain in Skewer Craftsmen in Botosari Hamlet, Dukuhmencek Village, Jember Regency - Adriani, Sri Wahyuni; Purwaningsih, Retno Ayu; Masturi, Indriyani Oktavia; Nuraini, Dyah Fita; Pradana, Antony; Bibi, Safira; Agustin, Dwi (Journal Of Humanities Community Empowerment, 2024)
Low back pain (LBP) is pain felt in the lower back, is not a disease or diagnosis for a disease but is a term for pain felt in the affected anatomical area with varying lengths of pain. Low back pain occurs due to incorrect working positions or vertebral loading that is three times heavier than in a standing position. The problem of low back pain arising from prolonged sitting is a frequent phenomenon at this time. Skewer craftsmen are at risk of Low Back Pain disease because they need a long time to sit. This counseling activity aims to make the skewer craftsmen know and understand about the prevention of Low Back Pain. The material presented contains understanding, causes, signs and symptoms, and prevention of Low Back Pain. The evaluation was carried out by giving questions in the form of pretests and posttests containing the same 10 questions and given to respondents to measure the level of knowledge before and after counseling. Based on the pretest and posttest that has been done, the results show that there is an increase in understanding in the skewer artisan community regarding Low Back Pain (LBP).